«Межотраслевой задачник» как инструмент содействия интеграции научного и производственного секторов в Республике Беларусь - Войтешонок, М. А. (БНТУ, 2019)
The article notes the importance of effective interaction between the scientific and industrial sectors for the innovative development of the country's economy. Intersectoral problem book is presented as an instrument for the integration of scientific and industrial sectors. Briefly reviewed the activities of university science in the framework of the Intersectoral problem book.